Change in renal biomarkers and in structural MRI outcomes in chronic kidney disease (CKD) patients over three years: Neuroimaging / differential diagnosis. (7th December 2020) - Murray, Anne; Vemuri, Prashanthi; Davey, Cynthia; Reid, Robert I.; Wille, Samantha M.; Thostenson, Kaely; Jack, Clifford R.; Knopman, David S.
Abstract: Background: We report the associations between change in renal biomarkers in CKD and non‐ CKD participants and change in structural MRI outcomes over 3 years in the BRain IN Kidney disease (BRINK) study MRI cohort. The imaging outcomes were cortical thickness in Alzheimer's disease signature regions, white matter hyperintensities (WMH), and fractional anisotropy in the corpus callosum (FA CC), an early marker of cerebrovascular disease. Methods: Participants were ≥ 45 years with CKD (estimated glomerular filtration rate (eGFR) in mL/min/1.73 m 2 < 60; non‐ dialysis) or non – CKD (eGFR ≥ 60) in Minneapolis/St. Paul. CKD severity was measured by the eGFR and urine albumin creatinine ratio (UACR‐albuminuria, a measure of microvascular disease). Brain images were obtained on a 1.5 T Phillips Ingenia machine at baseline and 3 years. Linear regression models measured the associations between 3 year change in eGFR and UACR, as predictors of change in MRI measures: AD cortical thickness, WMH, and FA CC over 3 years. Adjusted models included age, gender, AA race, education years, cerebrovascular disease risk factor score (CVD RF), smoker/alcohol use, and pulse pressure as covariates, and TIV for change in WMH models. Results: At baseline, mean age of the 97 participants was 67 years, and mean eGFR was 37 for the CKD group vs. 83.2 for non‐ CKD (Table 1). Mean change in eGFR and UACR in the CKD group were ‐3.6 and +212, respectively compared with ‐ 8.5 and +1.7 in the non‐ CKD group. Mean WMH volume increase (+5.8 cc) and mean FA CC decrease (‐0.012) were significant in CKD (p < 0.001) for both (Table 2). In adjusted models both a 1% decrease and a ≥ 3 unit/year decline in eGFR were associated with a decline in FA CC over 3 years in the CKD group (β (SE) =‐0.020 (0.007); p = 0.004) and ‐0.0097 (0.0042); p = 0.025, respectively). Cortical thickness models were not significant. Unexpectedly, change in UACR was not associated with change in any MRI outcomes. Conclusions: Decreased eGFR was associated with decreased FA CC in CKD, suggesting that CKD progression exerts its influence largely through cerebrovascular mechanisms.